SUCCESSFUL CORRECTION OF REFRACTORY ARTERIAL HYPERTENSION AND MORBID OBESITY IN PATIENT WITH SEVERE OBSTRUCTIVE APNEA SYNDROME - O. V. Tsygankova; E. M. Kalinina; L. D. Latyntseva; M. I. Voevoda (Российский кардиологический журнал, 2018)
.